Pemanfaatan Kamus Digital Arab-Indonesia sebagai Sumber Belajar Mahasiswa Institut Agama Islam Al-Zaytun Indonesia Tahun 2024 - Sofie Baetillah Sidkiyah; Irvan Iswandi; Iis Susiawati (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
Arabic language proficiency, a key element in Islamic religious education, requires adequate learning resources. One innovation that contributes to the learning process is the use of a digital Arabic-Indonesian dictionary. This study aims to identify the extent to which students utilize digital dictionaries and their impact on Arabic language learning. The study used a descriptive qualitative approach through data collection techniques such as observation, interviews, and documentation. Participants included students enrolled in the Arabic Language Education study program from the 2010 intake, lecturers teaching Arabic, and data on the use of digital dictionary applications. The study findings indicate that most students prefer using digital dictionaries due to their ease of access and comprehensive features, such as instant word search and examples of word usage in context. Students perceive digital dictionaries as more practical and efficient, especially for quickly searching for word meanings, which is very helpful in the intensive Arabic language learning process. However, several obstacles also arise, including low digital literacy among some students and limited internet access in some locations. On the other hand, lecturers at the Al-Zaytun Islamic Institute in Indonesia continue to encourage the use of printed dictionaries to train students' accuracy in searching for meanings, especially so that they do not rely solely on technology. Overall, the use of digital dictionaries has been proven to positively contribute to improving Arabic comprehension and sentence structure, making them an effective and relevant alternative learning resource in the digital age. The use of digital Arabic-Indonesian dictionaries also makes it easier for students to learn technical terms frequently used in academic and religious texts.